PREFERÊNCIA ALIMENTAR DE Spodoptera frugiperda POR GENÓTIPOS DE SORGO - BORTOLAZZO, Guilherme; DOURADINHO, Gabriel Zanuto; OLIVEIRA, Camilla Paulino de; ZOZ, Jardel; ZOZ, Andre; ZOZ, tiago (ANAIS DO ENIC, 2017)
-